2007
DOI: 10.1126/science.1146484
|View full text |Cite
|
Sign up to set email alerts
|

The Piwi-piRNA Pathway Provides an Adaptive Defense in the Transposon Arms Race

Abstract: Increasingly complex networks of small RNAs act through RNA-interference (RNAi) pathways to regulate gene expression, to mediate antiviral responses, to organize chromosomal domains, and to restrain the spread of selfish genetic elements. Historically, RNAi has been defined as a response to double-stranded RNA. However, some small RNA species may not arise from double-stranded RNA precursors. Yet, like microRNAs and small interfering RNAs, such species guide Argonaute proteins to silencing targets through comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
862
1
10

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 956 publications
(887 citation statements)
references
References 37 publications
14
862
1
10
Order By: Relevance
“…Furthermore, we observed that beta-geo, but not EGFP, was silenced, most likely because only neo, which has a sequence identical to beta-geo, lay in an orientation opposite to the piRNA precursor transcript and thus is expected to generate antisense piRNAs. Consistent with this, a majority of transposable elements in the piRNA precursors are found to be orientated in an antisense orientation (Aravin et al 2007a;Brennecke et al 2007). It is unknown, however, how the promoters of the precursor RNAs are regulated during the course of germ cell development to ensure piRNA generation at the time of retrotransposon expression.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, we observed that beta-geo, but not EGFP, was silenced, most likely because only neo, which has a sequence identical to beta-geo, lay in an orientation opposite to the piRNA precursor transcript and thus is expected to generate antisense piRNAs. Consistent with this, a majority of transposable elements in the piRNA precursors are found to be orientated in an antisense orientation (Aravin et al 2007a;Brennecke et al 2007). It is unknown, however, how the promoters of the precursor RNAs are regulated during the course of germ cell development to ensure piRNA generation at the time of retrotransposon expression.…”
Section: Discussionmentioning
confidence: 53%
“…Two piRNA biogenesis pathways exist, namely the primary and secondary pathways (Aravin et al 2007a;Kim et al 2009). In the primary pathway, piRNAs are derived from genomic regions termed piRNA clusters, of which size ranges from 1 to 100 kb in mice.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…All these strongly suggest that telsRNAs are pi-like RNAs associated with the telomeric heterochromatin. Previously reported piRNAs in mammalian cells are restricted to the male germ line, where Piwi family proteins (i.e., MIWI, MILI, and MIWI2) are specifically expressed (Aravin et al 2007a). The finding of pi-like tel-sRNAs in mouse somatic cells raises the question whether the Piwi-related slicer activity is present in cells other than male germ line cells.…”
Section: Resultsmentioning
confidence: 75%
“…Profound strand asymmetry of some piRNAs and their lack of Dicer dependence prompt the view that piRNAs are not generated from dsRNA precursors. Instead, a ping-pong model involving single strand RNA transcripts was proposed for the generation of piRNAs in Drosophila, as well as prepachytene piRNAs in mice (Aravin et al 2007a;Hartig et al 2007;Klattenhoff and Theurkauf 2008). Heterogeneous singlestrand noncoding RNA transcripts (TelRNA or TERRA) were reported to associate with telomeres in mice (Horard and Gilson 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation